2020
DOI: 10.12968/ijtr.2018.0148
|View full text |Cite
|
Sign up to set email alerts
|

The Son-Rise Programme: an intervention to improve social interaction in children with autism spectrum disorder

Abstract: Background/aims Communication problems are a core feature of autism spectrum disorder. These problems usually lead to challenges in social interactions. The aim of this study was to assess the effectiveness of the Son-Rise Programme on improving social interaction and communication in children with autism spectrum disorder. Methods Thirty children with autism spectrum disorder (aged 4–6) were involved in this study. The children were assigned randomly to one two groups, either the 1-week intensive Son-Rise Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These therapeutic approaches seek to strengthen children's communication, social interaction skills and reduce their stereotyped behaviors by joining the child's behaviors, playing with them, providing immediate feedback on social skills, and introducing new activities to continue communication and interaction skills. The results of various studies also confirmed that these methods improve communication and social interaction skills and reduce stereotyped behaviors in children with ASD (Kahjoogh et al, 2020;Bellini & Hopf, 2007).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These therapeutic approaches seek to strengthen children's communication, social interaction skills and reduce their stereotyped behaviors by joining the child's behaviors, playing with them, providing immediate feedback on social skills, and introducing new activities to continue communication and interaction skills. The results of various studies also confirmed that these methods improve communication and social interaction skills and reduce stereotyped behaviors in children with ASD (Kahjoogh et al, 2020;Bellini & Hopf, 2007).…”
Section: Discussionmentioning
confidence: 79%
“…Based on this study and the mothers study it is recommended that the Son-Rise program be performed in children with ASD by their mothers, especially the mother, as the primary caregiver. Kahjoogh et al (2020) in their study showed that the participants in the group of the Son-Rise Program showed a significant improvement in their social interaction skills compared to the control group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation